Analisis Gizi Buruk pada Lansia (Literature Review) - Salwana Salwana; Sultan Wirya; Yusril Isnandar; Marniati Marniati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Elderly is someone who has reached the age of 60 years and above, the menu is not a disease, but a continuous process that results in cumulative changes, is a process of decreasing the body's resistance in dealing with stimuli from within and outside the body. This study aims to systematically review and analyze various scientific literature related to the effect of nutritional intake on the nutritional status of the elderly, as well as the role of the family in meeting the nutritional needs of the elderly. The effects of malnutrition are also evident in social institutions such as nursing homes, where suboptimal nutritional management can improve malnutrition conditions. In other words, malnutrition has a negative impact on the biological, psychological, and social aspects of the elderly. Therefore, a holistic and integrated approach is needed to overcome this problem, including through educational interventions for families, psychological assistance, strict nutritional supervision, and support from a sustainable health service system.